TINJAUAN HUKUM PROGRESIF TERHADAP PEMBERIAN WASIAT WAJIBAH BAGI AHLI WARIS NON-MUSLIM - Fatahuddin Aziz Siregar (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2022)
This study aims to describe the problem of determining compulsory wills for non-Muslim heirs, this will be studied using a progressive legal perspective. While the type of   research used is qualitative research and is supported by literature research and uses a normative-juridical approach. The results of this study showed that the panel of judges of the Supreme Court considered that non-muslim heirs were entitled to a mandatory testamentary share of 1/4 or 25% of the property left by the testator. The reason is, heirs often accompany heirs both in good health, illness, and anything else entered when heirs seek treatment in China until heirs are willing to accompany them. Therefore, the practice of giving a compulsory will is a form of substantive justice to heirs as is characteristic of progressive law. Moreover, justice according to progressive law, it is not the state that asserts mechanisms but substantive justice.